The Effectiveness of Group Logotherapy on Developmental Challenges in Middle-Aged Married Women - Masiha, Solmaz; Khodayari Moghadam, Afsaneh (Psychology of Woman Journal, 2025)
Objective: The present study aimed to examine the effectiveness of group logotherapy on developmental challenges in middle-aged married women.Methods and Materials: Methodologically, this research employed a quasi-experimental design with a pre-test, post-test, and a control group. The statistical population consisted of middle-aged married women aged 40 to 65 years, residing in a 300-unit residential complex in District 2 of Tehran. A total of 30 participants were selected through convenience sampling and voluntary participation. The selected participants were randomly assigned to experimental and control groups, each consisting of 15 individuals. The experimental group received an eight-session intervention based on the logotherapy protocol within the framework of Schulenberg’s (2010) logotherapy model, while the control group received no intervention. Data collection was conducted using the Middle-Aged Developmental Challenges Questionnaire (Ali Roozbehani & Mahnaz Ali Akbar Dehkordi, 2017), which was administered as both a pre-test and post-test to both experimental and control groups. The data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 26. In the descriptive analysis section, statistical indices such as mean and standard deviation were employed. Additionally, to assess the normality of research variables, the skewness and kurtosis test was used, while Levene’s test was applied to examine the homogeneity of variances. In the inferential statistics section, univariate and multivariate analysis of covariance (ANCOVA) was utilized to compare the mean scores of the experimental and control groups while controlling for the effect of pre-test scores.Findings: The findings indicated that group logotherapy had a significant impact on the developmental challenges of middle-aged married women and its components.Conclusion: Group logotherapy significantly reduces midlife challenges in married women, improving their psychological well-being, adaptation to midlife crises, and enhancing life satisfaction by promoting meaning-seeking and responsibility.